SEMANTIC SHIFTS OF INDIAN LOANWORDS IN RUSSIAN: THE CORPUS AND ASSOCIATIVE ANALYSIS - Glukhova, Olga V.; Khachmafova, Zaineta R. (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
The study presents a comprehensive analysis of semantic changes in Indian loanwords within the Russian language, employing a mixed-methods approach combining corpus linguistics and psycholinguistic experimentation. The research analyzes a systematically compiled dataset of 83 lexemes, examining their frequency, collocational behavior. To outline the cognitive representation in Russian consciousness 6 most frequent loanwords were subjected to a free-association experiment with 135 native speakers. Grounded in theoretical frameworks linking semantic change to cognitive factors, the study specifically investigates the roles of word frequency and concreteness. The principal findings reveal a clear dichotomy in assimilation patterns. High-frequency, concrete loanwords demonstrate remarkable semantic stability, largely retaining their original meanings and showing predictable collocational patterns. In contrast, abstract and low-frequency terms, particularly from religious and philosophical domains, undergo profound semantic reconceptualization. The key transformations identified include: secularization of sacred concepts, metaphorical extension and semantic widening, development of pejorative connotations, and cultural re-attribution where modern Western cultural references displace original Indian cultural contexts. The research confirms that loanwords follow the same cognitive principles of semantic change as native vocabulary, with frequency and concreteness being primary determining factors. Methodologically, the triangulation of corpus data with associative experiment results proved particularly valuable, capturing emerging semantic shifts not yet fully conventionalized in written texts. The study concludes that lexical borrowing represents an active process of cognitive and cultural adaptation rather than passive assimilation, fundamentally reshaping conceptual structures through interaction with the recipient language’s cognitive and cultural environment. This research contributes to contact linguistics by providing an integrated framework for analyzing loanword assimilation across linguistic and cognitive dimensions.